What gaps exist in biomechanics and motor control research in Paralympic sports? A scoping review focussed on performance and injury risk - Lee, R.; Pinder, R. A.; Haydon, D. S.; Winter, L. M.; Crowther, R. G. (Journal of Sports Sciences, 2024)
In Paralympic sport, athletes, coaches and administrators seek medal-winning outcomes. Research in the fields of biomechanics and motor control can support the quantification of performance measures and injury risk. The aim of this article is to review the state of existing research and identify gaps offering researchers and practitioners targeted paths for creating competitive advantages. This review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR). Four electronic databases were searched in accordance with selected terms and inclusion/exclusion criteria. A custom data charting matrix was used to identify relevant characteristics. From the 3363 retrieved articles, 237 studies covering 24 Paralympic sports were included. A new metric, medal events per included study (MEPIS), was developed. Research gaps were identified in the sports studied, impairment types, gender balance, the injury reduction process, and the application of motor control research, leading to suggested directions targeting Paralympic success.